Love of life and its association with well‐being in Iranian psychiatric outpatients. Issue 6 (7th August 2020) - Dadfar, Mahboubeh; Abdel‐Khalek, Ahmed M.; Lester, David
Abstract: Aim: The aims of this study were as follows: (a) to investigate the psychometric properties of the Love of Life Scale (LLS); (b) to explore sex differences in LLS scores; (c) to explore LLS correlations with spiritual health and psychological well‐being; and (d) to compare the mean LLS score with previous studies. Design: A cross‐sectional study. Methods: A sample of 191 Iranian psychiatric outpatients was recruited from clinics at the School of Behavioral Sciences and Mental Health (Tehran Institute of Psychiatry), which is affiliated with the Iran University of Medical Sciences. They responded to the Farsi versions of the LLS, the Spiritual Well‐Being Scale (SWS) and the World Health Organization‐five Well‐Being Index (WHO‐5). Results: Cronbach alpha for the LLS was 0.95, and a principal component analysis (PCA) of the LLS items extracted one component labelled "Love of life." The sex difference in LLS scores was not significant. All the correlations between the scales were statistically significant and positive. Patients who had high scores for their love of life had better spiritual health and psychological well‐being. Discussion: The present sample obtained a lower mean LLS score than college students from eight countries except one. Further research should explore predictors of the love of life.